TABÚS INFORMATIVOS INDIVIDUALES Y ORGANIZACIONALES DEL PERIODISMO ESPAÑOL EN EL SIGLO XXI: UN ESTUDIO DELPHI* - Daniel BARREDO IBÁÑEZ (Fonseca, Journal of Communication, 2023)
The free speech of the Western democracies is assured by some legal, cultural and social elements. However we defend in this paper the existence of a determine number of topics which stop or restrict the free flow of information. We have defined them as ‘informative taboos’ because they share with the sociological restrictions a nature inherent, non-external, to the speakers. In this paper we have studied them from the point of view of the individual and organizational speaker inside of the Spanish context, a country where there was an official censorship until 1977. By the use of the methodology Delphi we have asked to seven Spanish experts in communication about the existence, the impact, the nature and also the possibilities of erosion of these barriers in the Spanish media.